A Fuzzy Logic-Based Energy Management Approach for Fuel Cell and Photovoltaic Powered Electric Vehicle Charging Station in DC Microgrid Operations - Cakmak, Recep; Bayrak, Gokay; Koc, Mehmet (Ieee-Inst Electrical Electronics Engineers Inc, 2025)
Hydrogen and electric vehicles (EVs) stand out as two promising technologies with the potential to revolutionize the future of transportation. The adoption of hydrogen and EVs indicates a noteworthy shift in the transportation paradigm, offering the prospect of reshaping this sector. This paper introduces an energy management approach based on fuzzy logic for a charging station that combines fuel cell (FC) and photovoltaic (PV) to power electric vehicles (EVs). The study emphasizes developing and simulating a fuzzy logic-based energy management system tailored for DC microgrid operations, including on-grid and islanded microgrid schemes. The system is designed and simulated in a digital simulation environment. The findings indicate that the fuzzy logic approach significantly enhances the performance of PV and FC-based EV charging stations. This research contributes to developing sustainable and efficient solutions for integrating electric vehicles and hydrogen-powered supply systems.
Keywords: Electric vehicle charging; energy management; fuel cell; fuzzy logic; photovoltaic power systems; energy management; fuel cell; fuzzy logic; photovoltaic power systems